Temporal variation in the population of bulbuls (Family Pycnonotidae) in lower montane forest, Northern Thailand - Yuwadee Ponpithuk; Supalak Siri; Mongkol Safoowong; Warong Suksavate; Dokrak Marod; Prateep Duengkae (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ponpituk Y, Siri S, Safoowong M, Suksavate W, Marod D, Duengkae P. 2020. Temporal variation in the population of bulbuls (Family Pycnonotidae) in lower montane forest, Northern Thailand. Biodiversitas 21: 3644-3649. Temporal variations in the population of bulbuls (Family Pycnonotidae) were studied over the course of four years in a 16-ha lower montane permanent plot, Northern Thailand. This study aimed to determine the relationship of the temporal variation of forest gaps with the population size of the bulbul, which plays a crucial role in seed dispersal and insect control in tropical forest ecosystems. This long-term monitoring study in a permanent plot was conducted monthly from January 2016 through October 2019. Data were collected using the mist-netting method for the capture-recapture protocol with individual bird banding. A total of 33,120 traps hour for 46 months,180 traps hour per day and 720 traps hour per month were recorded. The banding of a total of 94 individual bulbuls resulted in their classification into 5 species, consisting of Puff-throated Bulbul (Alophoixus pallidus), Mountain Bulbul (Ixos mcclellandii), Black-crested Bulbul (Pycnonotus flaviventris), Ashy Bulbul (Hemixos flavala) and Flavescent Bulbul (Iole virescens). The annual average density of bulbul for four years tended to decrease, but the difference was not significant. The highest average population occurred in 2016 and the lowest in 2018 with the changes being attributable to forest gap. Over time, monthly detection of bulbuls decreased gradually under closed canopy conditions, while in forest gaps, bird detection remained constant. As gap conditions so did detection probabilities. Our findings suggest that natural forest gaps can play an essential role as a temporal inhibitor to the rapid bird population decrease in the lower montane forest. This study will be useful for bird conservation and in balancing ecosystems for sustainability and providing interest in conservation initiatives requiring spatially explicit estimates of density.